Impact of the COVID-19 pandemic on the diagnosis of cancer in Japan: analysis of hospital-based cancer registries. (31st July 2022) - Okuyama, Ayako; Watabe, Mari; Makoshi, Riko; Takahashi, Hirokazu; Tsukada, Yoichiro; Higashi, Takahiro
Abstract: Background: There is significant concern that cancer care is adversely impacted due to the coronavirus disease pandemic. Using the national database, we document the impact of the pandemic on cancer diagnosis in Japan. Methods: Data from 735 hospital-based cancer registries, covering >70% of newly diagnosed cases, were analysed. We compared trends during 2016–2019 and those in 2020 by the type of cancer, diagnostic process, stage and 13 prefectures as requiring special precautions to prevent the spread of infection. Results: Overall, the number of patients who began treatment decreased by 1.9% in 2020 as compared with the average number during 2016–2019. A sharp decline of 13.8% was observed for stomach cases. The decline in cases (22.0% decrease for all cancers) was more pronounced in May. Cancer screening and resulting detection decreased significantly in 2020 (8.1–24.3%). Case registrations of stage I and II gastric cancer, stage II intrahepatic cholangiocarcinoma, stage II oesophageal cancer, stage 0 and I laryngeal cancer and stage II gallbladder cancer decreased by >10% compared with those in 2018 and 2019. The trends in cancer cases by area of residence indicated a decline in 13 prefectures in May 2020 compared with other areas. Conclusions: The number of cancer diagnoses decreased during the year 2020 under coronavirus pandemic, especially right after the Japanese government declared the first state of emergency in April. We need to carefully observe the consequences of these decrease in diagnosis, or perhaps the delay in care, on patient survival or population mortality. Abstract : The number of patients diagnosed with cancer who initiated treatment reduced since the Japanese government first declared the state of emergency in April during the COVID-19 pandemic.